2004
DOI: 10.1021/bi0488606
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Charged Residues and Hydrogen Bonds Tune the Ligand Histidine pKa Values of Rieske Iron−Sulfur Proteins

Abstract: Rieske proteins carry a redox-active iron-sulfur cluster, which is bound by two histidine and two cysteine side chains. The reduction potential of Rieske proteins depends on pH. This pH dependence can be described by two pK(a) values, which have been assigned to the two iron-coordinating histidines. Rieske proteins are commonly grouped into two major classes: Rieske proteins from quinol-oxidizing cytochrome bc complexes, in which the ligand histidines titrate in the physiological pH range, and bacterial ferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…However, several attempts have been made, especially of metal-bound water molecules, using the LD and PB methods. [18,24,27,31,35,36,40,43,44] The situation is analogous for reduction potentials, although the number of publications is smaller. Several scientists have tried to estimate the reduction potential of various groups in solution and in proteins, involving both metal sites and other redox-active cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…However, several attempts have been made, especially of metal-bound water molecules, using the LD and PB methods. [18,24,27,31,35,36,40,43,44] The situation is analogous for reduction potentials, although the number of publications is smaller. Several scientists have tried to estimate the reduction potential of various groups in solution and in proteins, involving both metal sites and other redox-active cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…However, several attempts have been made, especially for metal-bound water molecules, using the LD and PB methods. 32,34,[52][53][54] In this work, we study electron-and proton transfer reactions in the reaction cycle of the MCOs with the help of FEP calculations at the combined QM and MM (QM/MM) level. By estimating redox potentials, acidity constants, isomerisation free energies, as well as O 2 and water-binding free energies of putative intermediates, we obtain information about the most likely steps in the reaction mechanism, especially for the regeneration of the reduced state from the NI.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of the role of changes in pK introduced an additional constraint on the mechanism (15). In the work of Klingen and Ullmann (21), the pK a values of Rieske iron-sulfur clusters of bc-type and ferredoxin-type were calculated using density functional theory/electrostatic approaches based on the protein environment, and they suggested that the high E m and low pK a values in the former were largely determined by hydrogen bonding from these and other groups around the cluster.…”
mentioning
confidence: 99%